Ethics and Leadership: Examining the Roles of Honesty and Integrity - Muhammad Nabil Aditama; Ratih Purbasari; Sam'un Jaja Raharja; Herwan Abdul Muhyi (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2025)
Objective – This literature review aims to examine the importance of honesty and integrity in the practice and theories of leadership, and how both are fundamentally attached to the concept itself, particularly to the types of leadership that are characterized by the presence of ethics.Design/Methodology/Approach – It is written to elaborate the existing literatures on this very topic in a systematic manner and to examine them thematically, creating an organized discussions on how the understanding of the correlation of those two qualities with leadership developed.Findings – This paper elaborates on the very definition of leadership; how different perspectives may define the concept differently and how it shapes the practice of leadership itself. It highlights the gaps in previous theorization of transformational leadership and how it does not place heavy emphasis on moral values such as honesty and integrity. Furthermore, it explains the various perspectives on honesty and integrity and their connection to leadership, how the two qualities shape both the leader as the moral agent and the people or the organization as the extension of the given leader.Implications – Integrity and Honesty are indeed fundamental to leadership and its overall practice and theorization.